1997
DOI: 10.1074/jbc.272.8.4843
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity and Dimerization of Recombinant Human Estrogen Receptor Hormone-binding Domain

Abstract: The estrogen receptor dimerizes and exhibits cooperative ligand binding as part of its normal functioning. Interaction of the estrogen receptor with its ligands is mediated by a C-terminal hormone-binding domain (HBD), and residues within the HBD are thought to contribute to dimerization. To examine dimer interactions in the isolated HBD, a human estrogen receptor HBD fragment was expressed in high yield as a cleavable fusion protein in Escherichia coli. The isolated HBD peptide exhibited affinity for estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
4
38
2
1
Order By: Relevance
“…The nonlinear terms can then be neglected to give α ≈ −a 3 (K)/a 2 (K), and a good approximation to K corresponding to the largest possible α is given by K c in (40). In contrast to earlier work by Collier et al [4], Wearing et al demonstrated that the juxtacrine model (1) can generate a wide range of pattern wavelengths.…”
Section: Fastest Growing Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear terms can then be neglected to give α ≈ −a 3 (K)/a 2 (K), and a good approximation to K corresponding to the largest possible α is given by K c in (40). In contrast to earlier work by Collier et al [4], Wearing et al demonstrated that the juxtacrine model (1) can generate a wide range of pattern wavelengths.…”
Section: Fastest Growing Modesmentioning
confidence: 99%
“…In both the string and two-dimensional square arrays, K(λ) is bounded between ±1 as λ varies. However, K(λ) is reduced to [0,1] Substituting into the linearized model and dividing through by exp(αt + iλ · x), the condition for non-trivial solutions gives the cubic characteristic…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The 1:2 stoichiometry suggests that CaM may facilitate functional dimerization of ER-␣, which could help place two ER-␣ DNA binding domains in contact with tandem repeat sequences in ERE (36,37). The ER-␣ LBD (residues 305-552) forms a dimer in the x-ray crystal structure of the E2-bound state (12), whereas the E2-free apo-LBD has weaker dimerization affinity (38,39). Thus, ER-␣ dimerization stabilized by E2 binding may be important for activating transcription (3).…”
Section: Table 1 Itc Parameters For Cam Binding To Functional Fragmenmentioning
confidence: 99%
“…However, in reality the actual binding model could be more complicated because liganded ER is typically dimeric and therefore capable of binding two peptide motifs (one for each LBD in an ER homodimer). Based on the reported equilibrium constants for ER dimerization (37,38), we have assumed that, at the concentrations of ER and ER␣LBD used in this study (Ն16 nM), the receptor exists as a homodimer. To further simplify the system, we also immobilized limited amounts of each peptide to the chip surfaces so as to make it impossible for two peptides to bind simultaneously to a single ER homodimer.…”
Section: Spr Analysis Of Er␣lbd/lxxll Peptide Interactions-mentioning
confidence: 99%